SARS-CoV-2 and Plasmodium falciparum Co-Infection in a Returning Traveler - Huang, Qian; Xu, Wen-Jie; Wang, Xiao-Xiao; Zhang, Xuan; Pan, Ke-Nu; Zhang, Jia-Qi; Chen, Hua-Liang; Ruan, Wei; Yao, Li-Nong (Frontiers in Public Health, 2022)
Since December 2019, the Coronavirus Disease 2019 (COVID-19) pandemic has become a non-neglectable context for the whole healthcare system. Under the background of COVID-19, the detection and diagnosis of malaria cases are under challenge. Here, we reported a COVID-19 and malaria co-infection traveler who has a long living history in Cameroon. The case was administered with dihydroartemisinin and piperaquine tablets for malaria, Lopinavir and Ritonavir tablets, Arbidol, recombinant human interferon α-2b and Compound Maxing Yifei mixture for COVID-19, and Zolpidem Tartrate tablets, Diazepam, Paroxetine Hydrochloride tablets, Thymosin α1, and Lianhua Qinwen Jiaonang during the second hospitalization of the patient since the patient has a certain level of anxiety and insomnia with no evidence of inflammatory reactions. After being tested negative two times for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in 48 h, the patient met China's COVID-19 discharge standards and was discharged with stable vital signs and mental state. Since most countries in the sub-Saharan region have a fragile health system, co-infection for both Plasmodium and SARS-CoV-2 may not be uncommon, and raise a challenge in diagnosis, treatment, and prevention for both diseases. We add to the literature on co-infection of P. falciparum malaria and COVID-19 and offer operational advice on diagnosis, prevention, and treatment for the co-infection.